Overestimated inclinations of Milgromian disc galaxies: the case of the ultradiffuse galaxy AGC 114905. Issue 3 (19th April 2022) - Banik, Indranil; Nagesh, Srikanth T; Haghi, Hosein; Kroupa, Pavel; Zhao, Hongsheng
ABSTRACT: We present two hydrodynamical star-forming simulations in the Milgromian dynamics (MOND) framework of a gas-rich disc galaxy with properties similar to AGC 114905, which has recently been argued to have a rotation curve (RC) that is inconsistent with the MOND prediction. Our first model considers the galaxy in isolation, while our second model includes an external field of 0.05 a__0, the estimated gravitational field from large-scale structure. We show that isophotes in the face-on view can differ from circular at the 50 per cent level. This could mislead observers into overestimating the inclination i between disc and sky planes. Because RCs require a correction factor of 1/sin i, the actual RC could be much higher than that reported by observers. This plausibly reconciles AGC 114905 with MOND expectations.